PUBLIC ADMINISTRATION AND CORRUPTION IN ECUADOR; AN UNBEATABLE MARRIAGE - Ponce Franco, Janina; Rodríguez Rodríguez, Jessica Azucena; Cordovez Banderas, Armando Eriberto (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
Ecuador has witnessed critical situations regarding corruption throughout its history, this has meant instabilities of a political, economic and social nature, thus managing to counteract the well-being of its inhabitants. In the case to study, we proceeded to analyze the development of this nation from 2008 to 2018, considering international corruption indicators, which are International Country Risk Guide (ICRG), Worldwide Governance Indicators (WGI) and the Corruption Perception Index (CPI), selected for its greater functionality and use worldwide, which allowed to provide essential results to give an objective affirmation of the action by the government administration, identifying the presence of corruption in a manner quantitative The objective of the present investigation was to determine the existence in regard to the growth of corruption in the national territory, taking as a reference the results obtained in each year corresponding to the period studied, for which it was decided to work according to methodology quantitative with the help of the deductive method of investigation, it was possible to draw final conclusions.